Mass Distribution of Insecticide-Treated Nets: A Qualitative Study on Sumba Island - Patanduk, Yona; Rais Yunarko; Tallan, Mefi M.; Bulu, Anderias K.; Tangkelangi, Marni (Universitas Airlangga, 2024)
Background: The distribution of insecticide-treated nets (ITNs) is one of the main forms of malaria control intervention in Sumba Island. Although it has been running for more than a decade, there are still some gaps in the planning and implementation of this program. Aims: This study aims to obtain an overview of the planning and implementation of the mass distribution of ITNs running on Sumba Island, Indonesia. Methods: This study is qualitative research conducted in 2019 in all districts on Sumba Island. Data were collected by conducting in-depth interviews with 53 informants, including those in charge of the program, cross-sectors, and communities selected based on the researcher's considerations. Thematic analysis was used to produce the findings. Results: The study showed a gap between the number of ITNs and the real target, the sources of data on ITNs targets are different, and cross-sector involvement is limited to socialization activities, not maximizing the socialization and education of ITNs to the community. Conclusion: The planning and implementation of the mass distribution of ITNs on Sumba Island have not run optimally at the stages of socialization, logistics management, and distribution to the community. Modification of socialization methods and strengthening of distribution strategies to the community is needed.